Giant fibroepithelial polyp of the perineum: Giant fibroepithelial polyp. (2015) - Colak, Elif; Ikinci, Aygun; Kucuk, Gultekin Ozan; Kesmer, Sadik; Yildirim, Kadir
Highlights: Fibroepithelial polyps are among common benign skin lesions. They are seen rarely seen on the perineum. There is a small number of cases that reach the giant sizes in the literature. Abstract: Introduction: Fibroepitheial polyps (FEP) are among the most common benign skin lesions and definitive histology is often needed to exclude malignancy. These polyps are usually less than 5 cm in size and are often seen in genito-urinary sites including the perineum. A small number can reach a significant size. Presentation of case: A 46-year-old female patient presented with a pedunculated mass measuring 18 cm in diameter, localized to the left perineum. The lesion was excised and the histopathological diagnosis was fibroepithelial polyp. Conclusion: We present this case as the third largest FEP recorded in the available literature.